Bioequivalence of two novel formulations of ivermectin 1% combined with fluazuron 12.5% for subcutaneous administration in cattle - Diego M. Robaina; Silvana Alvariza; Gonzalo Suárez (GarVal Editorial Ltda., 2021)
Context: Ivermectin (IVM) and fluazuron are present as novel combinations to control ticks. Differences in formulations account for changes to the plasma kinetics and could change exposure of target parasites to active drugs. Aims: To evaluate bioequivalence for ivermectin administered by two novel formulations combined with fluazuron. Methods: Twelve male Holstein calves were randomized into two groups (n=6), receiving a single subcutaneous dose of a novel formulation (A or B) of ivermectin combined with fluazuron (ivermectin 1% 0.2 mg/kg + fluazuron 12.5% 2.5 mg/kg). Blood samples were taken until 34 days after dosing. Non-compartmental analysis was applied for bioequivalence assessment. Compartmental analysis was carried out and model acceptance was validated using the visual predictive check graphics. Results: Noncompartmental analysis shows that both formulations behaved similarly with Cmax ratio of 0.982 (CI90: 0.861 - 1.12, ANOVA test, p=0.814) and AUC0-t ratio of 1.01 (CI90: 0.97 - 1.05, ANOVA, p=0.586) but at different Tmax (1.4 ± 0.5 and 2.9 ± 1.2 days (Mann-Whitney U test, p=0.027) for A and B, respectively). The pharmacokinetic model has two compartments, linear elimination with first order absorption and formulation as covariable for the absorption rate. Conclusions: We conclude that the two novel formulations combined of IVM 1% with fluazuron 12.5%, are bioequivalent for administration of IVM in cattle. This shows that carrying out bioequivalence studies are of great importance for understanding the potential interchangeability between formulations available in the pharmaceutical market.